MARKET EFFICIENCY IN THE BELGRADE STOCK EXCHANGE - Ojdanic, Marija (My University, 2011)
The Belgrade Stock Exchange is the capital market operating in Serbia and Montenegro. It was established in 1989, but active share trading began only in around 2004. The purpose of this research was to test whether the Belgrade Stock Exchange exhibits random walk characteristics (non-predictability of future returns based on past returns), which is considered the minimum hurdle of market efficiency. The runs test and the LOMAC test were used to conduct the statistical tests. The sample consisted of the composite index of the Belgrade Stock Exchange and a selection of the largest, most liquid shares with sufficient trading history. Weekly, local currency data was used. Random walk hypothesis could not be rejected for the composite index nor for the majority of the selected shares, which lends support to the hypothesis that the Belgrade Stock Exchange is weak form efficient. This finding should increase international investors’ confidence in the Belgrade Stock Exchange and attract capital towards the country
MBA - WBS
Keywords: Stock exchange, Belgrade; Belgrade stock exchange